Pemberdayaan Santri Melalui Pelatihan Pembuatan Eco Enzym Dari Limbah Kulit Buah dan Sayur Sebagai Pupuk Cair - Syafrial; Mellyta Uliyandri; Delia Komalasari; Yahya Eko Nopiyanto; Yesa Elya Novia; Aldo David Dora (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2024)
This community service aims to improve the knowledge of students in making eco enzymes from fruit and vegetable peel waste as liquid plant fertilizer. A total of 16 male students at the Al Mubaarak Islamic Boarding School in Bengkulu were the subjects of the community service. The community service was carried out on August 3, 2024. Asset Based Community Development (ABCD) was chosen as the method for implementing community service activities consisting of 5 steps, namely: discovery, dream, design, define, and destiny. From the results of the activity, it is known that the average value of participant knowledge before the community service was carried out was 6.2; the average value of participant knowledge after the community service was carried out was 7.5. It can be concluded that this community service activity can improve the knowledge of students in making eco enzymes.